Answer:
the last picture
Step-by-step explanation:
the one where the line hits the -3 mark on the y-axis
Simplify
9x^3 - 4x + 10 + x^3 + 10x - 9
Collect like terms
(9x^3 + x^3) + (-4x + 10x) + (10 - 9)
Simplify
<u>10x^2 + 6x + 1</u>
Hello :
the general term is :
an = a1+(n-1)×d
or : an = ap +(n-p)×d......d is common diffrence
let : n=10 and p= 4
a10 = a4 +(10-4)×d
64 = 22 + 6d
6d = 42
d= 7
conclusion :
a4 = 22
a3 = 22-7=15
a2=15-7=8
a1= 8-7=1
<span>the first five terms : 1 , 8 , 15 , 22</span>
Answer:
0.06
Step-by-step explanation: